AN AUDIT OF MALIGNANT SOLID TUMORS IN INFANTS AND NEONATES - Sushmita N Bhatnagar (EL-Med-Pub, 2012)
Background: To audit the demographics, outcome and factors affecting long-term survival in infants and neonates with solid tumors.Material and Methods: Retrospective case series was performed for 13 years. Demographics, surgical notes, treatment protocols and outcome details were reviewed. Results: Of total 372 tumors over 13 years, there were 59 infants (15.86%) of which 8 were neonates, with M:F 1.2:1, and mean age of presentation was 5.18months. Fifty three of the infants had tumors which were > 5 cm in size. Thirty two (54%) had a rapid progression of the lesion during investigations. Tumors markers and pre-operative biopsy were diagnostic in 61.5% and 30% respectively. Neuroblastoma was the commonest tumor (22%), followed by hepatoblastoma (20.3%), malignant germ cell tumor (20.3%), soft tissue sarcomas (11.9%), and others (8.5%). Staging distribution for 39 (66%) infants showed Stage 1-n=9, Stage 2-n=15, Stage 3-n=7, Stage 4-n= 5 and Stage IVs-n=3. Nineteen (32.2%) babies received chemotherapy. Almost half (50.8%) of the children underwent surgical removal of the tumor; with gross total resection in 76.6%. The overall mortality was 35.6%. About 30.5% are alive, well and tumor free on 2-12 years follow-up. Conclusion: A much higher incidence (15.8%) of infantile tumors in our region as compared to literature (2%) is alarming. Treatment failures from deaths or non-compliance amounted to be 69.5%. These are the two major issues which need to be addressed in the future management of infantile tumors. Reduction in deaths due to chemotherapy toxicity, rapid surgical intervention and R0 resection and risk stratification needs to be incorporated, to improve long-term tumor free survival in infants.